From funding agencies to scientific agency: Collective allocation of science funding as an alternative to peer review - Bollen, Johan; Crandall, David; Junk, Damion; Ding, Ying; Börner, Katy (EMBO reports, 2014)
Graphical Abstract The traditional peer review system for grant proposals is not always optimal. A new crowdfunding proposal based on advances in technology and mathematics could improve efficiency while retaining peer judgement.